2020
DOI: 10.3390/nu12072138
|View full text |Cite
|
Sign up to set email alerts
|

The Modulation of Phase II Drug-Metabolizing Enzymes in Proliferating and Differentiated CaCo-2 Cells by Hop-Derived Prenylflavonoids

Abstract: Prenylflavonoids in the human organism exhibit various health-beneficial activities, although they may interfere with drugs via the modulation of the expression and/or activity of drug-metabolizing enzymes. As intestinal cells are exposed to the highest concentrations of prenylflavonoids, we decided to study the cytotoxicity and modulatory effects of the four main hop-derived prenylflavonoids on the activities and mRNA expression of the main drug-conjugating enzymes in human CaCo-2 cells. Proliferating CaCo-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…GSTA1-1 is highly expressed in many non-small-cell lung cancer cell lines and plays a crucial role in the development of anticancer drug resistance. Its downregulation leads to suppression of tumor growth and the induction of cell apoptosis [39,40]. Therefore, the downregulation of the GSTA1-1 mRNA expression caused by fisetin in proliferating CaCo-2 cells, observed in the present work, suggests a synergistic function of fisetin regarding the suppression and chemosensitization of cancer cells.…”
Section: The Effect Of Fisetin On Hgsta1-1 Expression and Inhibition supporting
confidence: 61%
“…GSTA1-1 is highly expressed in many non-small-cell lung cancer cell lines and plays a crucial role in the development of anticancer drug resistance. Its downregulation leads to suppression of tumor growth and the induction of cell apoptosis [39,40]. Therefore, the downregulation of the GSTA1-1 mRNA expression caused by fisetin in proliferating CaCo-2 cells, observed in the present work, suggests a synergistic function of fisetin regarding the suppression and chemosensitization of cancer cells.…”
Section: The Effect Of Fisetin On Hgsta1-1 Expression and Inhibition supporting
confidence: 61%
“…The differences in the effect of xanthohumol and the other hop-derived prenylflavonoids in proliferating and differentiated colorectal cancer cells (CaCo-2 cells) were demonstrated. In the latter, expression of phase II enzymes also showed specificity toward their isozymes, namely GST [ 42 ].…”
Section: Phytochemicals As Modulators Of Nrf2 and Nf-kb Signaling Pathwaymentioning
confidence: 99%
“…Taking into account the conclusions of Ambroz’s study [ 49 ], which reports antagonistic effects on concomitant administration of xanthohumol/chemotherapy, it was concluded that administration should be staged, in order to avoid decreasing the efficacy of the chemotherapeutics. It should be noted that other studies confirmed the cytotoxic action of other prenylflavonoids in hops on colonic proliferative cells, but xanthohumol had the most active contribution [ 50 ].…”
Section: Hops Antioxidants and Cancermentioning
confidence: 86%